El conocimiento objetivo como base para la educación según Karl R. Popper (2014)
The book entitled Objective Knowledge, was published in 1972. There, Popper collects a series of articles where he deals with the theory of knowledge. From these, it is possible to reconstruct the foundation for a critical education. This text aims to identify conceptual elements that relate to the increase of knowledge from the method of approach and problem solving, the role of language, the meaning of freedom, the development of a critical spirit and their implications of for political life. This is related to the educational process, so that students can approach the truth, appropriating their environment and pose increasingly optimal solutions to face the obstacles of everyday life and thus favoring the improvement of society.